Transforming agricultural straw waste into functional nanofibers via electrospinning: A sustainable approach - Bowei Tang; Zihao Xiong; Zheng Zhou; Dekun Lu; Ya Sun; Peipei Ding; Chunlei Wang; Juntao Yan (Journal of Agriculture and Food Research)
Agricultural waste straw is produced in large quantities annually, particularly in regions with high crop yields, such as rice, wheat and corn.The resource utilization of straw plays an important role in environmental protection, resource utilization, partial replacement of fossil energy and promoting agricultural carbon neutrality. Moreover, it's well known that electrospinning technology plays a vital role in enabling the conversion of straw-derived cellulose, lignin, hemicellulose and derivatives into high-value nanofiber materials. In this perspective article, we mainly focus on the separation of components and high-value conversion of agricultural waste straw. Specifically, the separation methods of agricultural waste straw components, the spinnability of cellulose, lignin, hemicellulose and derivatives, and the fabrication of straw-derivated functional electrospinning materials were introduced in detail, and these electrospinning fiber material are widely used in the fields of carbon fibers, environmental adsorption, energy storage, and biomedical materials, which provides a new perspective and strategy reference for the comprehensive utilization of straw biomass resources.